Anti-diabetic agents for prevention of type 2 diabetes mellitus in people with pre-diabetes: a systematic review and network meta-analysis protocol - Jiabin Liu; Hai Zeng; Guoxin He; Wenbin Fu; Xianzhe Wang; Lijin Huang; Rui Ma; Baile Ning (BMJ Open)
Introduction Type 2 diabetes mellitus (T2DM) is a substantial health problem worldwide. Pre-diabetic state is associated with increased risk for the development of diabetes. There are various pharmacological therapies with glucose-lowering activity for diabetes prevention. Of those, most are being compared with placebo instead of active agents. The relative effects and safety of different glucose-lowering drugs still remain uncertain. To address this gap, we will conduct a systematic review and network meta-analysis (NMA) to evaluate comparative efficacy and safety of glucose-lowering agents for T2DM prevention in patients with pre-diabetes.Methods and analysis PubMed, the Cochrane library and Embase will be searched from inception to December 2019 for relevant randomised controlled trials (RCTs) that examined anti-diabetic drugs for diabetes prevention in patients with pre-diabetes. Two reviewers working independently will screen titles, abstracts and full papers. Data extraction will also be completed by two independent authors. The primary outcome will be the incidence of T2DM in patients with pre-diabetes at baseline. Secondary outcomes will include the achievement of normoglycaemia, all-cause mortality, cardiovascular mortality and hypoglycaemic event. Pairwise meta-analysis and NMA will be conducted for each outcome using a frequentist random-effects model. Additionally, subgroup analyses will also be performed. The comparison-adjusted funnel plot will be used to assess publication bias. The overall quality of evidence will be rated with the Grading of Recommendations Assessment, Development and Evaluation framework. Data analysis will be conducted using Stata V.14.0.Ethics and dissemination Ethics approval is not required. We plan to submit the results of this study to a peer-review journal.PROSPERO registration number CRD42019119157.